Literal translation, functional equivalence and descriptive translation as strategies for translation of French and Czech legal terms - Honová, Zuzana (Comparative Legilinguistics, 2022)
In the process of deciding upon an appropriate equivalent for a legal term, the translator can choose between several possible strategies. The goal of the article is to analyse the translation strategies of French and Czech legal terms that do not have a direct equivalent in accessible terminographic sources of the target language. Among the possible strategies, it deals in particular with literal translation, functional equivalence and descriptive. It observes that all of the three strategies are used, to a greater or lesser extent, by the analysed terminographic sources and seeks to point out the problems that the use of each of the previously mentioned strategies may cause.